PUBLIC GOVERNANCE AND MUNICIPAL FINANCIAL HEALTH: AN INTEGRATED ANALYSIS WITH A FOCUS ON FINANCIAL PSYCHOLOGY AND TAX EDUCATION - Dantas, Luiz Antonio de Oliveira; Forte, Denis; Kadri, Nadia Wagih El (Seven Editora, 2026)
Objective: This study investigates the relationship between the effectiveness of municipal public management and the financial health of the population, considering levels of default, poverty, and social vulnerability in municipalities in the State of São Paulo. The article proposes a novel multidimensional model that integrates public governance, financial education, financial psychology, and behavioral science as determinants of collective financial well-being. Methodology: The research adopts a quantitative, exploratory, and explanatory approach. Only secondary data were used, extracted from official sources such as IBGE, IPEA, UNDP, Serasa Experian, and the Court of Auditors of the State of São Paulo (TCE-SP), covering the period from 2022 to 2024. Statistical analyses involved Pearson correlation techniques, multiple regression, and cluster analysis (K-means), allowing for the evaluation of the impact of the IEG-M dimensions (Planning, Fiscal, Education, Health, Environment, and Protected Cities) on default and social vulnerability indicators. Gap: Brazilian literature presents a deficit of empirical studies that explore, in an integrated way, the effects of local public governance on collective financial behavior and socioeconomic well-being. Few studies combine concepts from financial psychology, behavioral science, and municipal public management in the analysis of indebtedness and the financial health of the population. Results and Contributions: The results show that municipalities with better performance in planning (i-Plan), education (i-Educ), and fiscal management (i-Fiscal) have lower rates of default and social vulnerability. Multiple regression confirmed that these dimensions are significant predictors of municipal financial health. Cluster analysis classified the municipalities into three distinct groups, with different profiles of effectiveness and vulnerability. The study proposes an Integrated Multidimensional Model that articulates: (i) the quality of municipal governance; (ii) the local socioeconomic context; (iii) financial education and financial psychology interventions based on behavioral science; and (iv) the results in financial health and well-being of the population. This model expands the theoretical boundaries between public finance, economic psychology, and social policies.DOI: https://doi.org/10.56238/sevened2026.008-033